71. Impact of Prospective Audit and Feedback on Fluoroquinolone Use: A Large Academic Medical Center Experience. (31st December 2020) - Simon, Julio C; Vega, Ana
Abstract: Background: Fluoroquinolones are an effective class of antimicrobials; however, their use is not without consequence. Recent warnings have resulted in the FDA recommending to reserve this class for infections lacking alternative options. Antimicrobial stewardship significantly reduces targeted antimicrobial use, improves susceptibility patterns, decreases rates of Clostridium difficile infection (CDI), and reduces healthcare-associated costs. Literature on fluoroquinolone stewardship by antimicrobial stewardship programs report similar outcomes in addition to reductions in rates of extended-spectrum beta-lactamase (ESBL)-producing and methicillin-resistant S. aureus (MRSA) infection. Methods: This study was a retrospective cohort study of adult patients receiving at least 3 days of a fluoroquinolone for an indication of pneumonia or urinary tract infection. Retrospective orders were assessed for prescribing patterns, duration of therapy, and antibiotic choice by indication. The primary outcome was reduction of fluoroquinolone consumption as a result of a prospective audit and feedback intervention, determined with days of therapy (DOT) and DOT per 1000 patient days. Secondary outcomes included hospital length-of-stay (LOS), 3-month post-exposure incidence of CDI, ESBL and MRSA infections, percentage of interventions accepted, and QT prolongation events. Mann-Whitney U was used to determine statistical significance for DOT and LOS, unpaired student t-test was used for DOT per 1000 patient days. Results: 333 patients were reviewed. Fluoroquinolone median days-of-therapy (DOT) was significantly reduced in the intervention phase (7 vs. 4 days, P < 0.001). Median LOS was 8 days for the cohort and did not differ between groups. After adjusting for identifiable alternative causes, no difference in QT prolongation, CDI or ESBL infection was observed. However, these results were limited by lack of diagnostic testing for QT prolongation and inability to assess for other contributing factors related to infection control. Conclusion: Antimicrobial stewardship is an effective intervention to reduce fluoroquinolone use. An increased LOS was not observed despite patients switching to parenteral therapies. More data is needed to assess differences related to adverse events. Disclosures: All Authors : No reported disclosures